Controlled preparation of drug-exchange phase loaded polymeric fibres. Issue 1 (February 2012) - Sofokleous, Panagiotis; Chang, Ming-Wei; Ge, Ba Yin; Edirisinghe, Mohan; Stride, Eleanor
Abstract : Encapsulation of materials in fibres with a well-controlled size distribution is an important application of the electrospinning technique. This study investigates the effect of key parameters of the coaxial electrospinning process including flow rate, applied voltage and polymer concentration on the efficient encapsulation and size distribution of perfluorohexane (PFH) in polymethylsilsesquioxane (PMSQ) microfibres. Perfluorohexane can be exchanged for a drug via a simple diffusion-controlled process. By altering the polymer concentration and processing parameters, PMSQ microfibres with different diameters, PFH core size and core-to-core distance were obtained. It was found that PFH-encapsulated fibres with a diameter between 8 and 15 μm can be prepared when the PMSQ concentration is kept between 55–70 wt%. The PFH regions (cores) encapsulated in the fibre are uniformly distributed and of size 5–14 μm. The core-to-core distance significantly increased from 4 μm to 22 μm when the applied voltage was increased from 8 kV to 11 kV. These results indicate a potential strategy for controlling fibre diameter, core size and core-to-core distance by using coaxial electrospinning as the forming procedure and thus this work will help to advance biomedical engineering applications, for example, drug delivery, scaffolding for tissue engineering and wound dressing.